Assessment of the Influence of Voltage Unbalance on Three-Phase Operation of Power System (Nigerian Journal of Technology, 2021)
In the power system operation, efficient energy utilization is vital. However, with the advent of voltage unbalance, the system is faced with reduced efficiency in the process of energy conversion. This phenomenon occurs due to the asymmetrical behavior of the operating voltage phasor displacement and magnitudes. This occurrence has been attributed to a number of events; such as blown fuse which is as a result of unbalanced loading of the power factor correction capacitors, unbalanced source voltage, unequalled impedance in three-phase system, etc. Though, it is believed that the voltage unbalance phenomenon is more prevalent in the residential and commercial consumer supply. However, its impact on the industrial sector cannot be overemphasized. The power system operation of the induction motor; as the major energy conversion device; is modelled using the Park's transformation. This i s deployed to evaluate the influence of voltage unbalance by adopting the National Electrical Manufacturers Association (NEMA) and institution of Electrical and Electronic Engineering (IEEE) bench marking parameters for evaluating the system’s Voltage Unbalance Factor (VUF). The results show that the motor efficiency drop from 93.2% at 0% of voltage unbalance to 59.51% at 5% of unbalance. This suggests that the power system operation should be closely monitored to ensure that voltage unbalance is eliminated or mitigated by all means; so as to avoid loss of revenue to poor management of the system's power quality.